Diola ang bayani ng Philippine eagle ina ni Pag-Asa at Pagkakaisa = Heroine of Philippine eagles : mother of "Pag-Asa" and "Pagkakaisa" - Ordinario, Mary Ann; Ong, Yasmin S. (Plaridel St., Kidapawan City, Philippines ABC Educational Development Center, 2018)
Diola was a rescued Philippine Eagle that was raised in Monkey Eating Eagle Rehabilitation City in Davao City. She brought the Philippines recognition for being the first country to ever successfully hatch an egg from an eagle through artificial means. Diola was the mother of Pag-asa and Pagkakaisa.--Pumplepie: Books & Happiness.
"Handog ng may-akda kay Diola"--Title page.
"August 2018"--Title page verso.
Text in Filipino with English translation.
"Second prize winner [of the] Samsung Kids Time Author's Award : 2016 AFCC Singapore."--Cover.
Keywords: Monkey-eating eagle -- Philippines -- Juvenile literature; Endangered species -- Philippines -- Juvenile literature; Children's stories, Filipino; Children's stories, Philippine (English)